2016
DOI: 10.1016/j.jped.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Can procalcitonin be a diagnostic marker for catheter-related blood stream infection in children?

Abstract: The authors suggest that PCT could be a helpful rapid diagnostic marker in children with suspected CRBSIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…It was shown that moderately elevated PCT (1–2.5 ng/mL) could be found in CAP with positive blood culture for Streptococcus pneumoniae mainly in bacterial superinfection after an initial viral episode, possibly reflecting transitory immune impairment ( 33 ). Further, PCT has been shown to strongly correlate with sepsis and septic shock in neutropenic ( 35 , 36 ) and immune-competent patients ( 32 , 37 ). PCT is particularly good in differentiating bacterial from viral meningitis in children ( 38 ) and seems to be useful to rule-in pyelonephritis, but studies on urinary tract infections display a high heterogeneity, which is why PCT cannot be recommended for antibiotic management of urinary tract infections at this point.…”
Section: Procalcitoninmentioning
confidence: 99%
“…It was shown that moderately elevated PCT (1–2.5 ng/mL) could be found in CAP with positive blood culture for Streptococcus pneumoniae mainly in bacterial superinfection after an initial viral episode, possibly reflecting transitory immune impairment ( 33 ). Further, PCT has been shown to strongly correlate with sepsis and septic shock in neutropenic ( 35 , 36 ) and immune-competent patients ( 32 , 37 ). PCT is particularly good in differentiating bacterial from viral meningitis in children ( 38 ) and seems to be useful to rule-in pyelonephritis, but studies on urinary tract infections display a high heterogeneity, which is why PCT cannot be recommended for antibiotic management of urinary tract infections at this point.…”
Section: Procalcitoninmentioning
confidence: 99%
“… 7 There are multiple studies about its superiority to C-reactive protein (CRP) as an infection biomarker. Its utility has been demonstrated in invasive infections, 8 nosocomial infection (NI), 9 12 and after cardiopulmonary bypass. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…High PCT should serve to warn about nosocomial infection in those patients without other causes of higher PCT such as cardiopulmonary arrest and some kinds of surgeries, especially with PCT levels up to 2 ng/mL. 66 It is also useful for diagnosis of catheter-related-infection in those patients in whom other infections are also under study 75 (Table 4).…”
Section: • • Nosocomial Infectionsmentioning
confidence: 99%